FUNGSI PEMERINTAH DAERAH KABUPATEN KEPULAUAN MERANTI DALAM PEMBANGUNAN JALAN DI DESA MELAI KECAMATAN RANGSANG BARAT TAHUN 2013-2014 - Syaiful Fikri; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The background of this study by no completion of the construction of roads in the village to the village Melai Kedabu Rapat Meeting. The second village is an outlying village Government Kepulauan Meranti, so the road construction affects the lives of border communities. Development Planning Meeting Melai Kedabu Rapat already started in 2000, when the Government Bengkalis, however the project is dormant and unresolved. Meranti Islands District began planning the construction in 2013 until today the project has not been resolved The purpose of this study to determine function Meranti Islands District Government in the construction of the road.The method used is qualitative research. Qualitative research can be regarded as the research that produced the data descriptive of the words spoken and written san behavior that can be observed from the people studied. In the research problems using the theory of functions of government and local government management.Based on the analysis the authors of the roads in the village Melai, are not optimal Local Government in carrying out its functions, it can be seen from the Regional Government management is not maximized in the implementation of the road. The Local Government Management includes (planning, organizing, mobilization, monitoring and evaluation). Keywords: Function Government, Local Government Management in Rural Road Development ,, Melai